Treatment Of Chronic Kidney Disease Patients With A Supplemented Low Protein Diet And A Supplemented Very Low Protein Diet - SV Subhramanyam; A Nayak; PV Lakshmi; K S Nayak (The Korean Society of Nephrology, 2012)
The primary results of the Modification of Diet in Renal Disease were inconclusive and did confuse a lot of physicians about the dietary approach to CKD management. The study design was flawed and thus compromised the results and conclusions. Re-analysis of the MDRD study however clearly showed the benefits of dietary protein restriction and also more importantly an additional benefit by ketoanalogue supplementation in delaying progression of CKD. Despite the obvious benefits of protein restriction, concern has been raised recently especially patients on very low dietary protein (very-low-protein diets; VLPDs), which could lead to deterioration in the nutritional status of CKD patients. To address this particular issue of whether a sVLPD diet induces malnutrition the present study has been taken up 132 adult patients with Stage 3 to Stage 5 (Predialysis) were initiated on a protein restricted ketoanalogue supplemented diet after informed consent and the necessary Institutional Ethics Committee approvals. Based on their affordability, 92 patients randomly were assigned to the sLPD group whereby they received 0.6 G/Kg BW of dietary proteins supplemented by ketoanalogues at a dosage of one tablet per 10 Kg body weight. 40 patients received 0.3 G/Kg BW supplemented by ketoanalogues at a dose of one tablet per 5 Kg body weight. Renolog® tablets manufactured by La Renon Healthcare Ltd, Ahmebabad, India were prescribed as the ketoanalogue supplements. Renal, Metabolic, Nutritional parameters and Anthropometric analysis were done in both groups at the start of the study and at the end of 6 months of follow up. The mean blood urea in the SLPD group showed a decrease from 81.17+_ 00 mg/dl to 74.45+_30.75 mg/dl (p< 0.05) and in the SVLPD from 78.35+_00 mg/dl to 66.50+_34.50 mg/dl (p>0.05) at the end of six months indicating an improvement in renal function . The serum creatinine also showed a decrease from 3.52+_00 mg/dl to 3.30 +_1.63 mg/dl(p>0.05) in the SLPD group and a decrease from 3.74+_00 mg/dl to 3.55+_1.67 mg/dl(p>0.05) in the SVLPD group though not statistically significant. The eGFR showed improvement from 26.76+_00 ml/min to 30.75+_17.31 ml/min (p<0.05) at end of six months in the SLPD group and an increase from 23.62+_00 ml/min to 26.35+_10.58 ml/min(p>0.05) in the SVLPD group. Serum albumin increased from 3.85+_00 gm/dl to 4.00+_0.56 gm/dl (p<0.05) in the SLPD group and an increase from 4.03+_00 gm/dl to 4.07+_0.47 gm/dl in the SVLPD group indicating an improvement in nutrition in SVLPD group (p>0.05) . Blood hemoglobin increased from 11.18+_2.02 gm/dl to 11.48+_2.14 gm/dl in the SLPD group and an increase from 11.35+_0.96 gm/dl to 13.22+_1.03 gm/dl in the SVLPD group. Combined analysis of both the study groups together(SLPD +SVLPD) showed a statistically significant decrease in blood urea from 80.32+_0.0 mg/dl to 73.70+_31.81 mg/dl(p<0.05), decrease in serum creatinine from 3.59+_0.0 mg/dl to 3.38+_1.64 mg/dl (0>0.05) and increase in eGFR from 25.82+_ 0.0 ml/min to 29.42+_ 15.67 ml/min(<0.05) at the end of six months of therapy which was statistically significant indicating an improvement in renal function. The serum albumin increased from 3.91+_0.0 gm/dl to 4.02+_0.53 gm/dl (p<0.05) indicating a statistically significant improvement in nutrition. The protein restricted ketoanalogue treated patients in this large series showed significant improvement in their renal function, metabolic status and their extensively investigated nutritional parameters over a period of 6 months. The key here is to use the right dosage of the ketoanalogue supplements in addition to ensuring strict compliance of dietary restrictions. It is strongly recommended that ketoanalogues be routinely used in the conservative management of CKD.